Analysis of Heavy Metal Pollution in Rice and Its Status of Risk Assessment - Shasha JIANG; Yonghong HUO; Dehai LI; Ying MA; Rongchun WANG; Weihong LU (Shipin gongye ke-ji, 2023)
Rice not only plays an important role in people's daily diet, but also makes a huge contribution to China's agricultural products trade. However, heavy metal contamination in rice has become one of the main hazards about rice production and human health in China. In this paper, the main sources, existing forms, detection and analysis methods of heavy metal contamination in rice are reviewed, furthermore, the current situation, prevention and control measures, risk assessment of heavy metal contamination in rice are summarized. This review would provide a theoretical reference for the effective prevention and control, and the accurate risk assessment of heavy metal contamination in rice.